Unsur-Unsur Intrinsik Pendidikan Tauhid Dalam Cerpen Robohnya Surau Kami Karya A . A Navis - Sulung Aji Pangestu, Sulung Aji Pangestu (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2022)
Abstract The short story The Collapse of Surau Kami by A. A Navis is a short story which contains elements of monotheism education. A. A Navis is a writer from West Sumatra who is known as an outspoken figure, A.A. Navis in writing is focused on human and human problems such as suffering, bitterness, happiness and hope. This is done on the basis of intellectual awareness and not on the basis of any particular interest. The presence of A. A Navis in the world of Indonesian literature is considered not only as a great author, but also an author who voices the voice of Sumatra. This research is focused on the element of monotheism education in the short story